Semantic and Pragmatic Potential of Emojis in Context of a COVID-19 Pandemic - S. S. Zhdanov (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
In this paper, an attempt is made to analyze the semantic and pragmatic potential of emoji signs that explicate the “covid” meaning. The Internet thesaurus emoji with a common semantic component “medicine / coronavirus pandemic ”, circulating in the space of the Russian-speaking and English-speaking segments of the Internet serve as the material to be investigated. The authors of the article pose and analyze a number of significant issues to understand the role of emoji within the framework of pandemic discourse: the terminological variability of the terms smile, emoticon and emoji in the context of the described problems is clarified and specified; the structural and content potential of the emoji sign is characterized; the possibilities of the sign in the process of its use by of mass Internet culture carriers are determined; groups of emoji signs in the English-speaking and Russian-speaking segments of the Internet are distinguished and characterized. The authors use a field approach with the allocation of the core and periphery in the context of the description of the thematic thesaurus of emoji signs. In addition, attention is paid to the structural and semantic features of the emoji sign, which, ultimately, cause the appearance of a simple or complex pictogram. It is concluded that emoji signs are included in many social spheres of the Internet space within the general information context of the COVID-19 epidemic.